Assessment of the Biological Activity and Phenolic Composition of Ethanol Extracts of Pomegranate (Punica granatum L.) Peels - Željka Peršurić; Lara Saftić Martinović; Mladenka Malenica; Ivana Gobin; Sandra Pedisić; Verica Dragović-Uzelac; Sandra Kraljević Pavelić (Molecules, 2020)
Pomegranate (Punica granatum L.) is a rich source of constituents with confirmed strong biological activities. However, pomegranate peel, which encompasses approximately 30–40% of its weight, is treated as a biological waste. The aim of this paper was to evaluate the potential of pomegranate peel extracts and to propose its functional properties that can be used for development of functional products. Eight ethanol extracts of pomegranate peels (PPEs) were characterized by use of direct infusion quadrupole-time of flight (Q-TOF), and afterwards tested on their antioxidant, antibacterial and antiproliferative activities. Mass spectrometry analysis revealed that the most prevalent compounds in pomegranate peels were punicalagin, granatin and their derivatives. Analysed extracts had high total phenolic contents that ranged from 5766.44 to 10599.43 mg GAE/100 g, and strong antioxidant activity (7551.31–7875.42 and 100.25–176.60 μmol TE/100 g for DPPH and FRAP assays, respectively). The results of biological activity assays showed that all PPEs possessed antibacterial activity, and that S. aureus was the most sensitive specie with minimum inhibitory concentration and minimum bactericidal concentrations ranging from 0.8 to 6.4 mg/mL. Additionally, the analysis of antiproliferative activity revealed high potency of PPEs, as the IC50 values ranged from 0.132 mg/mL to 0.396 mg/mL. Multivariate analysis pointed out the most discriminative metabolites for antioxidant or antiproliferative activity. Overall, the pomegranate peel confirmed to be a highly valuable source of bioactive compounds that could be used to improve the food functional characteristics.